Gold(I) complexes of 9-deazahypoxanthine as selective antitumor and anti-inflammatory agents - Vančo, Ján; Gáliková, Jana; Hošek, Jan; Dvořák, Zdeněk; Paráková, Lenka; Trávníček, Zdeněk (PLoS One, 2014)
The gold(I) mixed-ligand complexes involving O-substituted derivatives of 9-deazahypoxanthine (HLn) and triphenylphosphine (PPh3) with the general formula [Au(Ln)(PPh3)] (1-5) were prepared and thoroughly characterized by elemental analysis, FT-IR and multinuclear NMR spectroscopy, ESI+ mass spectrometry, single crystal X-ray (HL5 and complex 2) and TG/DTA analyses. Complexes 1-5 were evaluated for their in vitro antitumor activity against nine human cancer lines, i.e. MCF7 (breast carcinoma), HOS (osteosarcoma), A549 (adenocarcinoma), G361 (melanoma), HeLa (cervical cancer), A2780 (ovarian carcinoma), A2780R (ovarian carcinoma resistant to cisplatin), 22Rv1 (prostate cancer) and THP-1 (monocytic leukaemia), for their in vitro anti-inflammatory activity using a model of LPS-activated macrophages, and for their in vivo antiedematous activity by λ-carrageenan-induced hind paw edema model on rats. The results showed that the complexes 1-5 exhibit selective in vitro cytotoxicity against MCF7, HOS, 22Rv1, A2780 and A2780R, with submicromolar IC50 values for 2 against the MCF7 (0.6 µM) and HOS (0.9 µM). The results of in vitro cytotoxicity screening on primary culture of human hepatocytes (HEP220) revealed up to 30-times lower toxicity of compounds against healthy cells as compared with cancer cells. Additionally, the complexes 1-5 significantly influence the secretion and expression of pro-inflammatory cytokines TNF-α and IL-1β by a similar manner as a commercially used anti-arthritic drug Auranofin. The tested complexes also significantly influence the rate and overall volume of the edema, caused by the intraplantar application of λ-carrageenan polysaccharide to rats. Based on these promising results, the presented compounds could qualify to become feasible candidates for advanced testing as potential antitumor and anti-inflammatory drug-like compounds.
Keywords: nádory; hypoxanthiny; Hypoxanthines; modely nemocí na zvířatech; spektroskopie infračervená s Fourierovou transformací; Humans; Anti-Inflammatory Agents; Antineoplastic Agents; nádorové buněčné linie; zvířata; Rats; Disease Models, Animal; protinádorové látky; zánět; edém; Spectroscopy, Fourier Transform Infrared; Gold; antiflogistika; Edema; Hepatocytes; krysa rodu Rattus; hepatocyty; Inflammation; Animals; lidé; Neoplasms; Cell Line, Tumor; zlato